Immunomodulation as a therapy for Aspergillus infection: Current status and future perspectives - Lauruschkat, Chris D.; Einsele, Hermann; Loeffler, Juergen (Journal of Fungi, 2018)
Invasive aspergillosis (IA) is the most serious life-threatening infectious complication of intensive remission induction chemotherapy and allogeneic stem cell transplantation in patients with a variety of hematological malignancies. Aspergillus fumigatus is the most commonly isolated species from cases of IA. Despite the various improvements that have been made with preventative strategies and the development of antifungal drugs, there is an urgent need for new therapeutic approaches that focus on strategies to boost the host’s immune response, since immunological recovery is recognized as being the major determinant of the outcome of IA. Here, we aim to summarize current knowledge about a broad variety of immunotherapeutic approaches against IA, including therapies based on the transfer of distinct immune cell populations, and the administration of cytokines and antibodies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Adaptive immunity; Aspergillus fumigatus; Cell therapy; Cytokine therapy; Fungal infections; Immunotherapy; Innate immunity; Invasive aspergillosis